Impact of etiology leading to abdominoperineal resection with anterolateral thigh flap reconstruction: A retrospective cohort study. Issue 1 (16th September 2022) - Meuli, Joachim N.; Hubner, Martin; Martineau, Jérôme; Oranges, Carlo M.; Guillier, David; Raffoul, Wassim; di Summa, Pietro G.
Abstract: Background: Large and deep perineal defects following abdominal perineal resection (APR) are a challenge for reconstructive surgeons. Even if generally performed for oncological reasons, APR can be indicated as well in extended infection‐related debridement for Hidradenitis suppurativa, Fournier's gangrene, or Crohn's disease. We aimed to compare the outcomes of two groups of patients with different indications for APR (infectious vs. oncological) after pedicled anterolateral thigh (ALT) flap coverage Results: Forty‐four consecutive pedicled ALT flap used for coverage after APR in 40 patients were analyzed. 26 patients (65%) underwent APR for oncological reasons and 14 patients (35%) for infectious reasons. The overall postoperative complications rate was significantly higher for infectious cases (76.5% vs. 40.7%, p = 0.0304). Major complications occurred in 52.9% of infectious cases versus 11.1% of oncological cases ( p = 0.0045). Obesity and infectious etiology were independent risk factors for overall and major complications, respectively. Conclusion: Patients undergoing APR for acute or chronic infections had significantly more overall and major complications than patients having oncological APR. Modified care might be considered, especially in obese patients, in terms of surgical debridement, antibiotic treatment modalities, and postoperative management.